Faktor-faktor Yang Mempengaruhi PAD Pada Pemerintah Daerah Se-Bakorwil Madiun - Nurharibnu Wibisono (Universitas Merdeka Madiun, 2020)
This research aims to analizying influencing Local Original Revenue to the regional government in the Madiun Regional Coordinating Board in 2010 - 2018. The independent variabels are the Local Tax, Local Retribution, the Result of Separted Regional Wealth Management, Other Legimate Local Original Revenue. The dependent variable is Local Original Revenue. This study uses secondary data Realized Local Government Budget from www.djpk.kemenkeu.go.id. Â The observation period from 2010- 2018 is carried out to the regional government in the Madiun Regional Coordinating Boardwhich includes Madiun Regency, Magetan Regency, Ponorogo Regency, Ngawi Regency, Trenggalek Regency, Tulungagung Regency, Pacitan Regency, Kediri Regency, Madiun City and Kediri City. The method of analysis used is multiple regression analysis with SPSS 20. The researsch result shows that the Local Tax influence to Local Original Revenue to the regional government of Madiun Regional Coordinating Board. Local Retribution influence to Local Original Revenue to the regional governmentof Madiun Regional Coordinating Board. The result of Separted Regional Wealth Management noÂ influence to Local Original Revenue to the regional governmentof Madiun Regional Coordinating Board. Other Legimate Local Original Revenue significant influence to Local Original Revenue to the regional governmentof Madiun Regional Coordinating Board.Keyword: Local Original Revenue, Local Tax, Local Retribution, The result of Separted Regional Wealth Management, Other Legimate Local Original Revenue.